2018
DOI: 10.3390/cells8010001
|View full text |Cite
|
Sign up to set email alerts
|

Can We Design a Nogo Receptor-Dependent Cellular Therapy to Target MS?

Abstract: The current landscape of therapeutics designed to treat multiple sclerosis (MS) and its pathological sequelae is saturated with drugs that modify disease course and limit relapse rates. While these small molecules and biologicals are producing profound benefits to patients with reductions in annualized relapse rates, the repair or reversal of demyelinated lesions with or without axonal damage, remains the principle unmet need for progressive forms of the disease. Targeting the extracellular pathological milieu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 126 publications
(178 reference statements)
0
10
0
Order By: Relevance
“…Additionally, gangliosides play a collaborative role in the signaling complex and have also been demonstrated to be important in preventing neuronal growth after spinal growth injury [80,81]. During neuroinflammation it has been demonstrated that NgR1-dependent signaling within spinal cord and optic nerve axons occurs through RhoA-GTP and the phosphorylation of the Rho-associated coiled-coil containing protein kinase 2 (ROCK II) to alter axonal transport and elicit neurodegeneration through downstream phosphorylation of the collapsin response mediator protein 2 (CRMP2) at the threonine 555 site located at its C-terminus [21,87]. Moreover, activation of NgR signaling through the binding of MAIFs present in extracellular myelin debris, can potentiate endogenous inhibitory effects on the maturation of oligodendroglial precursor cells (OPCs) and their recruitment around demyelinated plaques disrupting the remyelination process in progressive MS [77].…”
Section: Ngr Complex Signaling Pathways Interaction With Various Componentsmentioning
confidence: 99%
“…Additionally, gangliosides play a collaborative role in the signaling complex and have also been demonstrated to be important in preventing neuronal growth after spinal growth injury [80,81]. During neuroinflammation it has been demonstrated that NgR1-dependent signaling within spinal cord and optic nerve axons occurs through RhoA-GTP and the phosphorylation of the Rho-associated coiled-coil containing protein kinase 2 (ROCK II) to alter axonal transport and elicit neurodegeneration through downstream phosphorylation of the collapsin response mediator protein 2 (CRMP2) at the threonine 555 site located at its C-terminus [21,87]. Moreover, activation of NgR signaling through the binding of MAIFs present in extracellular myelin debris, can potentiate endogenous inhibitory effects on the maturation of oligodendroglial precursor cells (OPCs) and their recruitment around demyelinated plaques disrupting the remyelination process in progressive MS [77].…”
Section: Ngr Complex Signaling Pathways Interaction With Various Componentsmentioning
confidence: 99%
“…However, there is a lack of therapeutic approaches for secondary progressive MS (SPMS), a stage of the disease that follows RRMS. Moreover, available therapy options, which suppress or ablate the patient’s immune system, only slow disease progression but do not reverse neurological deficits [ 106 ]. Therefore, to improve treatment effectiveness and enhance patients’ quality of life, there is a pressing need for novel therapeutic approaches to restore neuronal function via promoting regeneration and remyelination.…”
Section: Nogo and Their Interacting Partners As Potential Therapeutic Targetsmentioning
confidence: 99%
“…This suggests that a gate in plasticity is lacking in the ngr1 −/− mice since the potent Nogo-A neurite outgrowth inhibitor expressed in mature oligodendrocytes in adulthood cannot limit the membrane-dependent dendritic or axonal varicosity formation. Therapeutics are being developed to target NgR1-dependent membrane interactions in various disease paradigms (for review see Petratos et al, 2012 ; Lee and Petratos, 2013 ; Lee et al, 2014 ; Kim et al, 2018 ). Therefore, it is important to dissect and define the precise mechanisms in which NgR1 can regulate plasticity at the axo-glial synapse.…”
Section: Nogo Receptor 1 (Ngr1) Regulates Neuronal Morphology and Synmentioning
confidence: 99%